Application of TF Nanoemulsion formulation for control of Pomacea maculata, pest of rice - Ibrahim, Muhammad Riduwan (2016)
Rice is the staple food for Malaysian. However, there are many pest and disease that attack rice. One of them is Apple snail (Pomacea spp.) which was categorized as one of the major pest on young rice seedlings. Use of chemical molluscicides by the rice farmers is a normal practice. Even though the effect of these synthetic molluscicides are quick and better, however they are not good for health as well as harmful to environment and human consumption. Saponin is a natural glycoside that can be found in most plants and it can be applied as a biomolluscicide which has lesser detrimental effects on human and the environment. TF nanoemulsion formulation containing saponin as bioactive ingredient was tested in this experiment on Pomacea maculata, to determine the efficacy of TF nanoemulsion formulation to control their population in rice field. The experiment was conducted in a paddy field located in Penang with four treatments. Two different concentrations of TF nanoemulsion formulation (10000 ppm and 20000 ppm) was used against water and niclosamide as control. The TF nanoemulsion formulation was applied before transplanting (with 5cm water level approximately). The mortality and rice damage assessment will be observed until all the snails died. Each treatment will be replicated ten times in 1m2 plot. Ten snails of 1 to 2 cm size will be used for each treatment in this experiment. Total snails used are 400. MR219 rice variety was used. Each plot was planted with 15 gram of paddy seedling and total of six kilograms rice seeds was used. RCBD was used as the experimental design. The data analyzed using Probit Analysis and Analysis of Variance (ANOVA). The result is TF nanoemulsion formulation has potential to function as new safer alternative molluscicide to control the P. maculata population in rice field.